The Historiography of the Polish Composers-Pedagogs on Podillia - Ozymovska, Hanna (Pedagogical Discourse, 2013)
In the article the vital and creative way of composers of the Polish origin is considered on Podillya of end of ХVІІІ – ХІХ of centuries – Vladyslav Zaremba, Tadeysh Ganutskiy, Anton Kotsipinskiy, Mykhajlo Zavadckiy. Pedagogical, concerto, musically-critical, elucidative activity of artists that carried out a ponderable contribution to further development of regional musical art is analyzed. Creative and pedagogical work of polish figures is investigational in basis of that the Podolsk folk song lies at stored traditions and carried them in instrumental music. The value of the Polish musicians is considered in development of professional musical culture and education on Podillya.